Project-Based Learning (PjBL) as a Strategy to Enhance Critical Thinking Skills in Elementary Students - Sirojuddin Abror; Siti Fatinnah (International Journal of Multidisciplinary Research and Innovation, 2025)
This study explores the implementation of Project-Based Learning (PjBL) as a strategy to enhance critical thinking skills among elementary school students in Jombang, Indonesia. The research is grounded in the belief that traditional teaching methods often limit students' cognitive engagement and problem-solving abilities. Through a qualitative case study design, data were collected from classroom observations, teacher interviews, and student project assessments in two elementary schools that have integrated PjBL into their curriculum. The findings reveal that PjBL encourages students to analyze, evaluate, and synthesize information in meaningful ways. Students demonstrated increased curiosity, collaboration, and the ability to formulate and defend their own ideas. Teachers reported improvements in classroom dynamics and student engagement, although challenges such as time constraints and the need for teacher training were noted. The study concludes that PjBL offers significant potential in developing critical thinking skills in young learners, especially when supported by appropriate instructional planning and professional development for educators. These results suggest that PjBL can serve as an effective pedagogical approach for primary education in Indonesia and similar educational contexts.